Synthesis of Zeolite from Fly Ash and Bottom Ash and Application for Biodiesel Transesterification - Putri, Rika; Goembira, Fadjar; Ulfah, Maria; Andrifar, Muhammad; Yuliarningsih, Rati; Aziz, Rizki (Jurnal Rekayasa Kimia & Lingkungan, 2024)
Burning coal in a Coal-Fired Power Plant produces by-products like fly ash and bottom ash. Zeolite synthesized from the ash in Teluk Sirih Coal-Fired Power Plant was applied as a catalyst in the biodiesel transesterification reaction. Zeolite synthesis used the hydrothermal method with acid pretreatment. The operating conditions for fly ash zeolite are a 2.4-molar ratio SiO2/Al2O3 and a crystallization time of 6 hours. The bottom ash zeolite used a 2.0-molar ratio SiO2/Al2O3 and a crystallization time of 8 hours. The performance test of the synthesized catalyst was carried out in the transesterification reaction using waste cooking oil as a raw material with a free fatty acid content of 0.7%. The synthesized catalyst was characterized using x-ray diffraction, scanning electron microscope, and Bruneuer-emmet-teller. The biodiesel with the highest yield was analyzed based on SNI 7182: 2015. The synthesis results of the catalyst produced type A zeolite, shown by the typical X-ray diffraction pattern and supported by the morphological test results using a cube-shaped. The surface area of zeolite fly ash and bottom ash is 12.87 m2/g and 5.13 m2/g. The test showed fly ash zeolite had the highest biodiesel yield of 89.66%. Based on the characterization using SNI 7182: 2015, the color and free glycerol met the standards, while density 40 C, kinematic viscosity 40 C, acid number, total glycerol, methyl ester content, and water content did not meet the standards.